2006
DOI: 10.1136/bjo.2006.100388
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the thickness of the human lamina cribrosa

Abstract: Objective: To measure the human lamina cribrosa thickness (LCT) in vitro in fully hydrated specimens and to determine whether there is any association between thickness and age or sex. Methods: 45 fixed human optic nerves, age range 9-90 years, were dissected from the globe and frozen sectioned. The study was divided into two parts: the first investigated the overall change in LCT and cribrosal beam thickness (CBT) with age, and the second divided eyes into two specific age groups (38-49 and 78-87 years) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 21 publications
2
47
2
1
Order By: Relevance
“…Although several previous studies reported that healthy males have thicker LCs than do females, this finding was not of statistical significance. 6,30 The present study also showed that male eyes have greater LTs than do female eyes, a finding not of statistical significance. Gender-specific differences may be due to differences in anatomical characteristics of the optic nerve head between genders, with males having slightly larger optic discs.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Although several previous studies reported that healthy males have thicker LCs than do females, this finding was not of statistical significance. 6,30 The present study also showed that male eyes have greater LTs than do female eyes, a finding not of statistical significance. Gender-specific differences may be due to differences in anatomical characteristics of the optic nerve head between genders, with males having slightly larger optic discs.…”
Section: Discussioncontrasting
confidence: 75%
“…5 Previous in vitro studies have revealed that laminar thickness (LT) increases significantly with age in the normal human globe, and that LCs of glaucomatous eyes are significantly thinner than those of normal eyes. 6,7 As the LC is on the posterior surface of the optic nerve head, it has been difficult to study due to technical limitations. With the recently developed combination of enhanced-depth imaging (EDI) optical coherence tomography (OCT) (EDI-OCT), visualisation of deep optic nerve head structures has improved.…”
Section: Introductionmentioning
confidence: 99%
“…The aged ONH is more likely to have stiff connective tissues [113][114][115][116][117][118][119][120][121][122][123][124][125] and a compromised blood supply 126,127 . However, age-related increases in laminar beam thickness 114,117,119,124,128 , laminar astrocyte basement membrane thickness 117,128 and laminar extracellular matrix (ECM) hardening 114,117,119,128 should not only increase laminar beam stiffness, but should also diminish nutrient diffusion from the laminar capillaries through the laminar ECM, across the astrocyte BMs, and into the adjacent axons (Figure 1).…”
Section: Onh Biomechanics Onh Aging and Age-related Optic Nerve Axonmentioning
confidence: 99%
“…However, age-related increases in laminar beam thickness 114,117,119,124,128 , laminar astrocyte basement membrane thickness 117,128 and laminar extracellular matrix (ECM) hardening 114,117,119,128 should not only increase laminar beam stiffness, but should also diminish nutrient diffusion from the laminar capillaries through the laminar ECM, across the astrocyte BMs, and into the adjacent axons (Figure 1). Thus, for a given magnitude of IOP insult, the aged ONH should demonstrate: 1) less deformation due to the presence of a stiffer lamina and peripapillary sclera; and 2) more pallor for a given amount of deformation because a) the aged ONH may be more susceptible to axon loss and b) pallor precedes deformation in the aged eye, while deformation precedes (or supersedes) pallor in the young eye.…”
Section: Onh Biomechanics Onh Aging and Age-related Optic Nerve Axonmentioning
confidence: 99%
See 1 more Smart Citation